Perencanaan CAD CAM Mesin CNC Milling Router 3 Axis Dengan Perangkat Lunak Mastercam - Fahlevi, Muhammad Reza; Syafri, Syafri; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
A CNC (Computer Numerically Controlled) machine is a machine tool that can work automatically. The CNC machine sends operational instructions that are inputted via a computer that is directly connected to the machine. This CNC machine uses PC (Personal Computer) as main control with windows platform for Operation System (OS). The CNC programming becomes an important element of the machine in work. The numerical signals are inputted into the Mach3 software as the main controls for the movement of axis (axes) x, y, and z as well as spindles. EIA-RS 274D programming format or G & M codes are used in this study for further adjustment of characters per character so that bug error does not occured on Mach3. Therefore, a CNC machine programming plan is created to adjust the machine, which can work according to the design of the Mastercam software. Mastercam software is selected because it has the completeness to design and obtain program instructions with simulation. Mastercam is a full-featured modeling software that combines 2D and 3D frame and surface geometry with editing and transformation capabilities. The G & M codes were generated by Mastercam that would be adjusted by removing G2 and G3 commands, which circular or unidirectional motion commands. In conclusion, this research revealed the program adjustment and program execution of a CNC program creating with CAD CAM system into the interface, therefore the CNC machine can be controlled by the PC device.Key words : CNC, Mastercam, G & M Codes, Mach3